2014
DOI: 10.1103/physreve.89.042705
|View full text |Cite
|
Sign up to set email alerts
|

Modular network evolution under selection for robustness to noise

Abstract: Real networks often exhibit modularity, which is defined as the degree to which a network can be decomposed into several subnetworks. The question of how a modular network arises is still open to discussion. The leading hypothesis is that high modularity evolves under multiple goals, which are decomposable to subproblems, as well as under the evolutionary constraint that selection prefers sparse links in a network. In the present study, we investigate an alternative evolutionary constraint entailing increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Models of (Leclerc ; Burda et al ; Friedlander et al. ; Ikemoto and Sekiyama ) and data about (Proulx et al. ; Winterbach et al ) genetic and metabolic networks provide parallel evidence for selection to shorten and simplify information pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Models of (Leclerc ; Burda et al ; Friedlander et al. ; Ikemoto and Sekiyama ) and data about (Proulx et al. ; Winterbach et al ) genetic and metabolic networks provide parallel evidence for selection to shorten and simplify information pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Models of (Leclerc 2008;Burda et al 2010;Friedlander et al 2013;Ikemoto and Sekiyama 2014) and data about (Proulx et al 2005;Winterbach et al 2013) genetic and metabolic networks provide parallel evidence for selection to shorten and simplify information pathways. Actual networks tend to be sparse and modular as compared to randomly generated networks.…”
Section: Selection On the Information Pathwaymentioning
confidence: 99%
“…The emergence of modularity has received less research than the emergence of networks (e.g. Ikemoto & Sekiyama, 2014; Kashtan & Alon, 2005) and, once again, tends to be information‐theoretical rather than based on biological principles or mechanisms (Root‐Bernstein & Dillon, 1997; Simon, 1981). Part of the difficulty is historical.…”
Section: Introductionmentioning
confidence: 99%
“…Biologically, however, the gene networks are known to be sparsely connected [1]. It has been shown that robustness to expression noise is positively correlated with network modularity [2]. Since a high modularity implies low connections between modules, the networks can be maintained to be sparse in noisy environments.…”
Section: Introductionmentioning
confidence: 99%